2022
DOI: 10.1021/acs.jmedchem.2c01586
|View full text |Cite
|
Sign up to set email alerts
|

RGD Peptide-Conjugated Dodecaborate with the Ga-DOTA Complex: A Preliminary Study for the Development of Theranostic Agents for Boron Neutron Capture Therapy and Its Companion Diagnostics

Abstract: A boron neutron capture therapy (BNCT) system, using boron-10-introduced agents coupled with companion diagnostics, is anticipated as a promising cancer theranostic. Thus, this study aimed to synthesize and evaluate a probe closo-dodecaborate-(Ga-DOTA)-c(RGDfK) (16) [Ga = gallium, DOTA =1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid, and c(RGDfK) = cyclo(arginine-glycine-aspartate-d-phenylalanine-lysine] containing closo-dodecaborate ([B12H12]2–) as a boron cluster, a [67Ga]Ga-DOTA derivative for nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…DOTA chelating agent was chosen due to its excellent chelating properties toward both 68 Ga (PET/CT diagnostics) and 177 Lu (radionuclide therapy) radioisotopes and its numerous examples of successful biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…DOTA chelating agent was chosen due to its excellent chelating properties toward both 68 Ga (PET/CT diagnostics) and 177 Lu (radionuclide therapy) radioisotopes and its numerous examples of successful biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…23,24 Conjugation of CPP with PTX can not only improve the water solubility of PTX (avoiding the use of inorganic solvents such as Cremophor EL) but also enhance the delivery of PTX into tumor tissues, thus inhibiting drug resistance. 25,26 One such recently reported promising CPP is an effective, short-chain dual-targeting cyclic heptapeptide probe (having sequence c[RGDKLAK]) that consists of both tumor-homing motifs (RGD) 13 coupled with a proapoptotic motif (KLA). 27 This peptide probe can specifically interact with α v β 3 -integrin receptors highly expressed on endothelial cells as well as many types of tumor cells, most specifically brain tumor glioblastoma cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhao et al studied the effect of PLGA-encapsulated PTX conjugated with PEG-DMA as a delivery system and observed that a high therapeutic dose (3 μg/mL) is required for treatment even after resection of GBM . Mishiro et al reported the development of a theranostic agent [c­(RGDfK)- 67 Ga-DOTA-dodecaborate] for boron neutron capture therapy (BNCT) and observed that the proposed agent is not problem-free, as observed from some viable tumor cells left due to heterogeneity in accumulation in tumor tissues . Furthermore, the hydrophobicity (lower BBB penetration) of PTX limits its use as an efficient first-line chemotherapeutic drug that needs primary consideration when designing PTX-based formulations. , Hence, these issues give rise to the necessity to divert the attention of researchers for designing novel hydrophilic tumor-specific peptide-based PTX formulations (except the ideology of nanoformulations) to kill cancer cells efficiently with as much as possible reduced side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium mercaptoundecahydro- closo -dodecaborate (BSH), which is a boron cluster containing 12 boron atoms, was used for the treatment of glioma. , l -Boronophenylalanine (BPA) is currently the most-used boron agent in clinical BNCT because it is selectively taken up in tumors through l -type amino acid transporter 1 (LAT1) overexpressed in various cancer cells. ,, Moreover 18 F-labeled BPA-based positron emission tomography (PET) is available to estimate pharmacokinetics of BPA, enabling the prediction of the appropriate timing of neutron irradiation after administration of BPA. , However, it remains challenging to apply BNCT to tumors that express low levels of LAT1. To broaden cancer indications of BNCT, boron agents with different delivery mechanisms from BPA have been developed. …”
Section: Introductionmentioning
confidence: 99%